Selective Imaging of Matrix Metalloproteinase-13 to Detect Extracellular Matrix Remodeling in Atherosclerotic Lesions - Buchler, Ariel; Munch, Maxime; Farber, Gedaliah; Zhao, Xiaoling; Al-Haddad, Rami; Farber, Eadan; Rotstein, Benjamin H (Université d'Ottawa | University of Ottawa, 2022)
Overexpression and activation of matrix metalloproteinase-13 (MMP-13) within atheroma increases susceptibility to plaque rupture, a major cause of severe cardiovascular complications. In comparison to pan-MMP targeting [18F]BR-351, we evaluated the potential for [18F]FMBP, a selective PET radiotracer for MMP-13, to detect extracellular matrix (ECM) remodeling in vascular plaques possessing markers of inflammation.
Keywords: Atherosclerosis; Autoradiography; Inflammation; Matrix metalloproteinases; Positron emission tomography; Radiotracer; Remodeling; Vulnerable plaques; Animals; Extracellular Matrix; Matrix Metalloproteinase 13; Mice; Tissue Distribution; Atherosclerosis; Plaque, Atherosclerotic